The gospel according to St John the authorized version with introduction and notes. - Westcott, Brooke Foss, 1825-1901 (Grand Rapids, MI Eerdmans, 1881)
Includes bibliographical references.
Originally published as part of the Speaker's Commentary. Reprints : Copy 1 : 1967; copy 2 : 1978.
Keywords: Bible. N.T. John -- commentaries